Genetically engineered mouse models of prostate cancer. Issue 2 (14th February 2013) - Parisotto, Maxime; Metzger, Daniel
Abstract : Despite major improvement in treatment of early stage localised prostate cancer, the distinction between indolent tumors and those that will become aggressive, as well as the lack of efficient therapies of advanced prostate cancer, remain major health problems. Genetically engineered mice (GEM) have been extensively used to investigate the molecular and cellular mechanisms underlying prostate tumor initiation and progression, and to evaluate new therapies. Moreover, the recent development of conditional somatic mutagenesis in the mouse prostate offers the possibility to generate new models that more faithfully reproduce the human disease, and thus should contribute to improve diagnosis and treatments. The strengths and weaknesses of various models will be discussed, as well as future opportunities.